B cells require type 1 interferon to produce alloantibodies to transfused KEL-expressing RBCs in mice - Gibb, David R. (Transfusion, 2017)
BACKGROUND: Alloantibodies to RBC antigens can cause significant hemolytic events. Prior studies have demonstrated that inflammatory stimuli in animal models and inflammatory states in humans, including autoimmunity and viremia, promote alloimmunization. However, molecular mechanisms underlying these findings are poorly understood. Given that type 1 interferons (IFNα/β) regulate antiviral immunity and autoimmune pathology, the hypothesis that IFNα/β regulates RBC alloimmunization was tested in a murine model. STUDY DESIGN AND METHODS: Leuko-reduced murine RBCs expressing the human KEL glycoprotein were transfused into control mice (WT), mice lacking the unique IFNα/β receptor (IFNAR1(−/−)), or bone marrow chimeric mice lacking IFNAR1 on specific cell populations. Anti-KEL IgG production, expressed as mean fluorescence intensity (MFI), and B cell differentiation were examined. RESULTS: Transfused WT mice produced anti-KEL IgG alloantibodies (peak response MFI=50.4). However, the alloimmune response of IFNAR1(−/−) mice was almost completely abrogated (MFI=4.2, p<0.05). The response of bone marrow chimeric mice lacking IFNAR1 expression in all hematopoietic cells or specifically in B cells was also diminished (MFI=3.8 and 5.4, respectively, compared to control chimeras, MFI=65.6, p<0.01). Accordingly, transfusion-induced differentiation of IFNAR1(−/−) B cells into germinal center B cells and plasma cells was significantly reduced, compared to WT B cells. CONCLUSIONS: This study demonstrates that B cells require signaling from IFNα/β to produce alloantibodies to the human KEL glycoprotein in mice. These findings provide a potential mechanistic basis for inflammation-induced alloimmunization. If these findings extend to human studies, patients with IFNα/β-associated conditions may have an elevated risk of alloimmunization and benefit from personalized transfusion protocols.